Treatment of Depression in Children Through Expressive Writing Therapy - Nurul Hafizah; Indahria Sulistyarini (Psikostudia : Jurnal Psikologi, 2024)
Depression in children is a psychological problem that is often ignored and left untreated. This condition can have an impact on children's decreased desire to eat, loss of interest in children and cognitive impairment that can disturb the development of children. This study aims to determine the effectiveness of expressive writing therapy on reducing the intensity of depression in children. This study uses a research design, namely single-case research. The subject in this study was a 12-year-old girl who experienced symptoms of depression as measured using the Children Depression Inventory (CDI). The diagnosis was given after assessing the subject in the form of interviews, observations and comprehensive psychological tests. The researcher determines the baseline related to the subject's psychological condition in determining the intervention. The results showed that there was a decrease in the intensity of the main symptoms of depression in the subject, then there were changes in thoughts, feelings and behavior in the subject before and after the intervention of expressive writing therapy on the subject. Depresi pada anak merupakan salah satu permasalahan psikologis yang sering diabaikan dan sering tidak diobati. Kondisi ini dapat berdampak kepada penurunan nafsu makan pada anak, kehilangan ketertarikan pada anak hingga adanya penurunan kognitif yang dapat mengganggu proses perkembangan pada anak. Penelitian ini bertujuan untuk mengetahui efektivitas terapi menulis ekspresif terhadap penurunan intensitas depresi pada anak. Penelitian ini menggunakan desain penelitian yaitu single-case research. Subjek dalam penelitian ini merupakan seorang anak perempuan berusia 12 tahun yang mengalami gejala depresi yang diukur dengan menggunakan Children Depression Inventory (CDI). Diagnosis diberikan setelah dilakukan asesmen kepada subjek berupa wawancara, observasi dan tes psikologi secara komprehensif. Peneliti menentukan baseline terkait kondisi psikologis subjek dalam menentukan intervensi. Hasil penelitian menunjukkan bahwa terdapat penurunan intensitas gejala utama depresipada subjek dan terjadi perubahan secara pikiran, perasaan dan perilaku pada subjek pra serta pasca intervensi expressive writing therapy pada subjek.